Feeling better? – Identification, interventions, and remission among women with early postpartum depressive symptoms in Sweden: a nested cohort study - Karin Gidén; Lisa Vinnerljung; Stavros I. Iliadis; Emma Fransson; Alkistis Skalkidou (European Psychiatry, 2024)
Abstract